Promoting Solar Energy through Auctions : The Case of Uganda - Meyer, René (World Bank, Washington, DC, 2015)
Uganda has just completed the first donor-subsidized competitive bidding program for grid connected solar photovoltaic (PV) generation in Sub-Saharan Africa. Uganda’s GET FiT Solar Facility will provide a performance-based subsidy of USc 5.37/kWh to lower the cost to Ugandan consumers of the electricity produced from four 5 MW solar plants bid by two developers at an average price of USc 16.37/kWh. This note analyzes the bidding process and the lessons learned, for possible replication in other developing countries in Sub-Saharan Africa and elsewhere.